2016
DOI: 10.3758/s13414-016-1226-0
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic convergence across multiple measures and model talkers

Abstract: This study consolidates findings on phonetic convergence in a large-scale examination of the impacts of talker sex, word frequency, and model talkers on multiple measures of convergence. A survey of nearly three dozen published reports revealed that most shadowing studies used very few model talkers and did not assess whether phonetic convergence varied across same-and mixed-sex pairings. Furthermore, some studies have reported effects of talker sex or word frequency on phonetic convergence, but others have fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 103 publications
9
103
0
Order By: Relevance
“…The large interindividual variability is consistent with previous reports showing that convergence may not equally distribute across dyads (Pardo, Urmanche, Wilman, & Wiener, 2017). The large interindividual variability is consistent with previous reports showing that convergence may not equally distribute across dyads (Pardo, Urmanche, Wilman, & Wiener, 2017).…”
Section: Behavioral Results and Gmm-ubm Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…The large interindividual variability is consistent with previous reports showing that convergence may not equally distribute across dyads (Pardo, Urmanche, Wilman, & Wiener, 2017). The large interindividual variability is consistent with previous reports showing that convergence may not equally distribute across dyads (Pardo, Urmanche, Wilman, & Wiener, 2017).…”
Section: Behavioral Results and Gmm-ubm Performancesupporting
confidence: 91%
“…Although convergence (phonetic alignment) is a well-known phenomenon, its quantitative assessment is still an open area of research. Therefore, a great deal of inconsistency and variability still exists among studies (Pardo, Urmanche, Wilman, & Wiener, 2017). Therefore, a great deal of inconsistency and variability still exists among studies (Pardo, Urmanche, Wilman, & Wiener, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to small sample size, their results on inspiration of imitation were inconclusive, though they found that women more readily perform and detect imitation than men. Other studies, however, have found contradictory gender patterns (Pardo, 2006) or even failed to reproduce gender differences in imitation at all Pardo, Urmanche, Wilman, & Wiener, 2017). Pardo's (2006) study is one that complicates findings regarding a straightforward effect of gender on imitative behavior by suggesting that other socio-situational factors might interact with gender.…”
Section: Social Sensitivitymentioning
confidence: 89%
“…Due to small sample size, their results on inspiration of imitation were inconclusive, though they found that women more readily perform and detect imitation than men. Other studies, however, have found contradictory gender patterns (Pardo, ) or even failed to reproduce gender differences in imitation at all (Pardo et al, ; Pardo, Urmanche, Wilman, & Wiener, ).…”
Section: Interventionists: Evidence To the Contrarymentioning
confidence: 96%